A water-soluble cyclometalated iridium(III) complex with fluorescent sensing capability for hypochlorite. (December 2019) - Lu, Zhen; Shangguan, Mingqin; Jiang, Xingzong; Xu, Peiyao; Hou, Linxi; Wang, Tao
Abstract: Herein, a novel cyclometalated iridium (III) complex (Ir-1 ) with good water-solubility was designed and synthesized to sensitively detect hypochlorite (ClO − ) in aqueous buffer solution. The sensorIr-1 was prepared by incorporating a methacrylate group into cyclometalated ligands, which was a specific response site toward ClO − through an oxidation process.Ir-1 displayed strong emission at 615 nm, while significant fluorescence quenching was observed upon addition of ClO − with a low detection limit of 0.41 μM. Moreover, probeIr-1 exhibited a rapid response (<30 s) for ClO − with high selectivity over potentially competing species. The sensing process was evidenced by NMR and MS characterization. Further application in bioimaging of ClO − was successfully performed in living HepG2 cells. Graphical abstract: Image 1 Highlights: A water-soluble fluorescent probe based on cyclometalated iridium (III) complex was designed and synthesized. The probe displayed a fast response toward ClO − (<30 s) with a low detection limit of 0.41 μM. The probe showed high selectivity toward ClO − over other reactive oxygen species. The probe was successfully applied for bioimaging of ClO − in living cells.